Significance of furosemide in patients with cirrhosis treated with or without zinc acetate hydrate supplementation. Issue 5 (21st February 2022) - Uchida, Yoshihito; Uemura, Hayato; Tsuji, Shohei; Yamada, Shunsuke; Kouyama, Jun‐ichi; Naiki, Kayoko; Sugawara, Kayoko; Nakao, Masamitsu; Nakayama, Nobuaki; Imai, Yukinori; Tomiya, Tomoaki; Mochida, Satoshi
Abstract: Background: The Japanese guidelines for the treatment of cirrhosis suggest zinc supplementation to prevent hepatic encephalopathy in patients with cirrhosis and zinc deficiency, although the factors that are associated with therapeutic efficacy remain unknown. Method: A total of 159 patients with chronic liver diseases but without previous zinc supplementation were analyzed. Factors associated with serum zinc levels as well as the therapeutic efficacy of zinc supplementation were evaluated. Result: Serum zinc levels decreased with the progression of liver diseases. A multiple linear regression analysis revealed that the serum levels of albumin and cholinesterase and the daily furosemide dose were independently associated with the serum zinc levels. The optimal furosemide cut‐off dosage for patients with zinc deficiency (<60 μg/dl) was 5 mg/day. Among 34 patients receiving zinc acetate hydrate, overt hepatic encephalopathy occurred in 12 patients (35.4%). A multivariate analysis identified a minimal serum zinc level of 50 μg/dl after more than 12 weeks of zinc supplementation as a factor associated with overt encephalopathy development, while furosemide use was not associated. The Child‐Pugh score at baseline was the only factor associated with the maintenance of sufficient serum zinc levels. Conclusion: Although the furosemide dose was negatively correlated with the serum zinc level in patients with chronic liver diseases, furosemide use was not associated with the occurrence of overt encephalopathy in those receiving zinc supplementation. Serum zinc levels of ≥50 μg/dl were required to prevent overt encephalopathy development during zinc supplementation in both patients with and those without furosemide administration.